The Great Obstetrical Syndromes and the Human Microbiome—A New Frontier - Solt, Ido (Rambam Health Care Campus, 2012)
Over the last two decades, advanced molecular genetics technology has enabled analysis of complex microbial communities and the study of microbial genomics. Interest has grown in characterizing the microbiome, defined as a collective microbial community and its extensive genome, as a clue to disease mechanisms. “The Human Microbiome Project,” sponsored by the NIH Common Fund, was established to characterize the pathology-associated human microbiome in nasal passages, oral cavities, skin, the gastrointestinal tract, and the urogenital compartment. In particular, characterization of urogenital microbiota may elucidate etiologies of complex obstetrical syndromes and factors in fetal development that define risk for pathology in adulthood. This article summarizes recent findings defining the microbiome associated with the female urogenital compartment in child-bearing age women. We also describe our analysis of microbiome samples from the oral, vaginal, and rectal compartments in a cohort of pregnant women. Findings present technical considerations in the characterization of microbial diversity and composition associated with gestational diabetes as a model pregnancy-associated pathology.